TINJAUAN PERENCANAAN PROYEK PEMBANGUNAN GEDUNG / RUANG BARU PUSKESMAS MANDIANGIN KOTA BUKITTINGGI - Muhammad Irfan; Ishak Ishak; Surya Eka Priana (Ensiklopedia Research and Community Service Review, 2022)
In general the upper structure includes beams, columns, floor plates and roofs that serve to support the loads that work on a building. The calculations that will be carried out on the construction of Building / New Room of Served Medicine Puskesmas District Mandiangin Bukittinggi in 2021 are floor plates, beams and columns. Structural expenses (dead loads, life loads) are guided by SNI 03-2847:2002 and earthquake loads are guided by SNI 03-1726:2012, where portals are calculated and modeled using the ETABS 2018 program. The purpose of this calculation is to get an idea of the basic principles of planning and reviewing the structure of the building, comparing the results of the calculation of the author with the results of the calculation of the planner consultant. From the calculation results obtained the largest moment on the B1 beam of 131.8420 kN-m and the largest moment in column K1 (50 x 30 cm) of 194,827 kN-m. For floor plates there is a repeating difference: 120 mm thick floor plate, ø 10- 160 mm for direction x and direction y author, floor plate 120 mm, ø 10- 250 mm for direction x and direction y planner, column K1 (50 x 30 cm) 16 D 19 and planner has 16 D 16, for column K2 there are differences in dimensions and bones i.e. : Column K2 (45 x 25 cm) 16 D 19 author, column K2(50 x 30cm) 16D 16 planner. For B1 and B2 blocks there are differences in dimensions and bones namely: beam B1 (45 x 25 cm) 6 D 19 authors, B1 beam (50 x 30 cm) 5 D 19 planner, B2 beam (40 x 25 cm) 6 D 19 author, B2 beam (45 x20 cm) 4 D 19 planner. Keywords : Column Structure, Beam, Floor Plate, Charging, ETABS2018, Reinforcement